2001
DOI: 10.1074/jbc.m106207200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Kinesin-related Protein, KRMP1, as a Target for Mitotic Peptidyl-prolyl Isomerase Pin1

Abstract: Mitosis utilizes a number of kinesin-related proteins (KRPs). Here we report the identification of a novel KRP termed KRMP1, which has a deduced 1780-amino acid sequence composed of ternary domains. The amino-terminal head domain is most similar to the kinesin motor domain of the MKLP-1 subfamily and has an intrinsic ATPase activity that is diminished by substituting the consensus Lys-168 with Arg. The central stalk domain is predicted to form a long ␣-helical coiled-coil, and can interact with each other in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 35 publications
2
24
0
Order By: Relevance
“…MPHOSPH1 was previously reported to interact with mitotic peptidyl-prolyl isomerase (Pin1) protein in Homo sapiens (24). However, because the Pin1 expression was undetectable in bladder cancer cells in our microarray data and semiquantitative RT-PCR analysis (data not shown), we attempted to identify protein(s) interacting with MPHOSPH1 in bladder cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…MPHOSPH1 was previously reported to interact with mitotic peptidyl-prolyl isomerase (Pin1) protein in Homo sapiens (24). However, because the Pin1 expression was undetectable in bladder cancer cells in our microarray data and semiquantitative RT-PCR analysis (data not shown), we attempted to identify protein(s) interacting with MPHOSPH1 in bladder cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…Kif20b is highly similar to its sister Kinesin-6 proteins Kif23 and Kif20a in the motor head domain, but divergent in the stalk and tail, predicting different cargo binding (Miki et al, 2005). The only proteins shown to interact with KIF20B during cytokinesis, PIN1 and PRC1, are upstream regulators (Kamimoto et al, 2001;Kanehira et al, 2007;Lee et al, 2012;Lu and Zhou, 2007). Other candidate cargos of Kif20b (Maliga et al, 2013;Sapir et al, 2013) do not have known roles in cytokinesis.…”
Section: Et Al 2001) It Is Not Yet Clear Whether Most Tissues Do Nmentioning
confidence: 93%
“…Kif20b, by contrast, is vertebrate specific, and its role in cytokinesis is less understood. Kif20b was originally cloned as a mitotic phosphoprotein called Mphosph1, MPP1 (Matsumoto-Taniura et al, 1996;Westendorf et al, 1994) or KRMP1 (Kamimoto et al, 2001). KIF20B knockdown in dividing human cell lines did not disrupt cytokinetic furrowing, but increased abscission failures (Abaza et al, 2003;Kanehira et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In searching for novel HCC targets that potentially increase chemotherapy efficacy, we focused on the kinesin protein MPHOSPH1, first identified through its in vivo interaction with the mitotic peptidyl-prolylisomerase PIN1 (30). In the current study, we investigated the efficacy of the combined treatment of targeting MPHOSPH1 in combination with taxol in HCC xenograft models, and demonstrated that reducing endogenous MPHOSPH1 significantly enhanced the cytotoxic effect of taxol against HCC, which suggests that MPHOSPH1 is a potential target for HCC therapy.…”
Section: Discussionmentioning
confidence: 99%